Anti-Inflammatory Functions of Protein C Require RAGE and ICAM-1 in a Stimulus-Dependent Manner - Natascha Braach; Kirsten Buschmann; Johanna Pflaum; Hannes Hudalla; Lutz Koch; Eduard Ryschich; Johannes Poeschl; David Frommhold (Mediators of Inflammation)
By binding β2-integrins both ICAM-1 and the receptor for advanced glycation end products (RAGE) mediate leukocyte recruitment in a stimulus-dependent manner. Using different inflammatory mouse models we investigated how RAGE and ICAM-1 are involved in anti-inflammatory functions of protein C (PC; Ceprotin, 100 U/kg). We found that, depending on the stimulus, RAGE and ICAM-1 are cooperatively involved in PC-induced inhibition of leukocyte recruitment in cremaster models of inflammation. During short-term proinflammatory stimulation (trauma, fMLP, and CXCL1), ICAM-1 is more important for mediation of anti-inflammatory effects of PC, whereas RAGE plays a major role after longer proinflammatory stimulation (TNFα). In contrast to WT and Icam-1−/− mice, PC had no effect on bronchoalveolar neutrophil emigration in RAGE−/− mice during LPS-induced acute lung injury, suggesting that RAGE critically mediates PC effects during acute lung inflammation. In parallel, PC treatment effectively blocked leukocyte recruitment and improved survival of WT mice and Icam-1-deficient mice in LPS-induced endotoxemia, but failed to do so in RAGE-deficient mice. Exploring underlying mechanisms, we found that PC is capable of downregulating intracellular RAGE and extracellular ICAM-1 in endothelial cells. Taken together, our data show that RAGE and ICAM-1 are required for the anti-inflammatory functions of PC.